2010
DOI: 10.1108/02683941011023721
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of politics and fairness in merit pay

Abstract: Purpose: Employee perceptions of politics and fairness were studied in a work setting where a new merit pay system had recently been implemented.Design/methodology/approach: Based on the literature on organizational politics, equity, procedural justice, and social exchange theory, we expected that employee perceptions of politics and fairness are associated with the perceptions of merit pay effectiveness. The results are based on employee survey responses from three governmental organizations (N=367) that had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 76 publications
(128 reference statements)
4
24
0
1
Order By: Relevance
“…Special private bonuses in the manufacturing business reveal employee perceptions of interpersonal justice from the supervisor-subordinate relationship related to direct experiential rewards. These results are in agreement with the notions of Andersson-Strberg et al, 77 Salimäki and Jämsén, 78 St-Onge, 79 and van Dijke et al 80 that employees perceive distributive, procedural and interpersonal justice in direct rewards.…”
Section: Inquiry Results: Direct Rewards and Experiential Patternsupporting
confidence: 94%
“…Special private bonuses in the manufacturing business reveal employee perceptions of interpersonal justice from the supervisor-subordinate relationship related to direct experiential rewards. These results are in agreement with the notions of Andersson-Strberg et al, 77 Salimäki and Jämsén, 78 St-Onge, 79 and van Dijke et al 80 that employees perceive distributive, procedural and interpersonal justice in direct rewards.…”
Section: Inquiry Results: Direct Rewards and Experiential Patternsupporting
confidence: 94%
“…In other words, in a country like Pakistan, most of the employees are not completely aware about organizational politics and its influence on their job performance and involvement. Previous studies support our findings suggesting that organizational politics and employees' commitment are negatively related and that employees' commitment and performance are positively related and the negative relationship between organizational politics and job involvement (Salimaki and Jamsen, 2010;Karadal and Arasli, 2009;Chang et al, 2009;Vigod, 2000). Based on the above findings, it can be concluded that public sector employees' of Pakistan are affected by organizational politics.…”
Section: Discussionsupporting
confidence: 89%
“…The potential contribution of this study exists in the new direction which improving the employee performance and involvement by increasing their commitment level with organizations in public sector arena. Organizational politics and employees' commitment are positively related with satisfaction and employees' commitment and performance are also positively related (Salimaki & Jamsen, 2010). The objective of this study is to find the impact of organizational politics on employee's job performance, employee's job involvement and employee but positively effected the higher standard employees (Witt, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…The Cronbach's alpha reliability coefficient of the scale was .86. A similar perceptual measure of compensation system effectiveness has been used in previous studies (e.g., Balkin and Gomez-Mejia 1990;Salimäki and Jämsén 2010).…”
Section: Compensation System Effectivenessmentioning
confidence: 99%